3D printed functional cookies fortified with Arthrospira platensis: Evaluation of its antioxidant potential and physical-chemical characterization. (October 2020) - Vieira, Marta V.; Oliveira, Sara M.; Amado, Isabel R.; Fasolin, Luiz H.; Vicente, Antonio A.; Pastrana, Lorenzo M.; Fuciños, Pablo
Abstract: In the last few decades, consumers' growing attention to the close relationship between health and nutrition is emerging as a new trend, mostly regarding the incorporation of natural ingredients into food. Among those ingredients, microalgae are considered as innovative and promising compounds, rich in valuable nutrients and bioactive molecules. In the present work, 3D printed cookies were fortified with the microalga Arthrospira platensis aiming at developing a new functional food with antioxidant properties. A. platensis antioxidants were recovered using ultrasound-assisted extraction in hydroalcoholic solutions. Ethanol/water and biomass/solvent ratios were optimised through a Design of Experiments (DOE) approach, using the antioxidant activity (ORAC and ABTS) and total phenolic content (TPC) as response variables. The highest ORAC, ABTS and TPC values were observed in the extract obtained with 0% ethanol and 2.0% biomass; thus, this extract was chosen to be incorporated into a printable cookie dough. Three different incorporation approaches were followed: (1) dried biomass, (2) freeze-dried antioxidant extract and (3) antioxidant extract encapsulated into alginate microbeads to enhance the stability to heat, light, and oxygen during baking and further storage. All dough formulations presented shape fidelity with the 3D model. The cookies had aw values low enough to be microbiologically stable, and the texture remained constant after 30 days of storage. Moreover, the extract encapsulation promoted an improvement in the ORAC value and colour stability when compared to all other formulations, revealing the potential of A. platensis for the development of a functional 3D food-ink. Graphical abstract: Image 1 Highlights: Antioxidant extraction from the microalga A. platensis was optimised using DoE. Edible inks were made using encapsulated microalgae extracts and food hydrocolloids. All cookie dough formulations (edible inks) were suitable for 3D food printing. 3D printed cookies exhibited colour, texture and microbiological stability over time. Extract encapsulation improved cookies antioxidant potential and colour stability.